Niobium rod quality and its impact on the production of Nb3Sn strand for the Divertor Tokamak Test Facility toroidal coils. Issue 1 (1st May 2022) - Smathers, D.; Flanigan, J.; Kim, J.; Sim, K.
Abstract: Niobium Tin cable is being used in the high field magnets in the Divertor Tokamak Test Facility under construction by ENEA in Italy. Kiswire Advanced Technology was selected to provide 55 tonnes of high-performance Niobium Tin wire for the 18 Toroidal Field Coils. The conductor design is based on a 0.82mm Nb3 Sn strand similar to that provided for the ITER TF coils. H. C. Starck Solutions provided the pure Nb rod and Ta sheet for their conductor design. The enhanced strand requirement has both a minimum current (320 A at 12 Tesla) and maximum hysteresis loss (± 3T cycle 1000mJ/cc) and a Cu/Non-Cu of 1:1. To achieve the current and hysteresis loss reliably, the niobium rod must maintain its shape throughout the drawing process. The n value requirement (>20) is a good indication of niobium filament uniformity while the RRR requirement (>100) is a good indication of tantalum barrier performance. The HCSS rod supplied to KAT provided consistently high Ic (>320A at 12 Tesla), low hysteresis loss and the Ta sheet provided very good RRR values. We report here the consistency of more than 11 tonnes of HCSS Nb rod properties for chemistry, hardness, grain size and wire performance.